It is, if the following works:
(f@(g@h))(x) = ((f@g)@h)(x)(f∘(g∘h))(x)=((f∘g)∘h)(x)
That is, if:
f(x) = "something"f(x)=something
g(h(x)) = (g@h)(x) = "something else"g(h(x))=(g∘h)(x)=something else
f(g(x)) = (f@g)(x) = "something else again"f(g(x))=(f∘g)(x)=something else again
h(x) = "something else yet again"h(x)=something else yet again
...and you can use these together to satisfy the first expression, then they are associative. Let:
f(x) = 2xf(x)=2x
g(x) = x^2g(x)=x2
h(x) = x^3h(x)=x3
Thus:
g(h(x)) = g(x^3) = (x^3)^2 = x^6g(h(x))=g(x3)=(x3)2=x6
f(g(x)) = g(x^2) = 2(x^2) = 2x^2f(g(x))=g(x2)=2(x2)=2x2
Then:
(f@(g@h))(x) = f(x^6) = 2(x^6) = color(blue)(2x^6)(f∘(g∘h))(x)=f(x6)=2(x6)=2x6
((f@g)@h)(x) = f(g(x^3)) = f((x^3)^2) = f(x^6) = color(blue)(2x^6)((f∘g)∘h)(x)=f(g(x3))=f((x3)2)=f(x6)=2x6
Therefore they are associative.